Zealot [compact disc, unabridged] : the life and times of Jesus of Nazareth - Aslan, Reza (Random House, Inc., 2013)
"A fascinating, provocative, and meticulously researched biography that challenges long-held assumptions about the man we know as Jesus of Nazareth. Zealot yields a fresh perspective on one of the greatest stories ever told even as it affirms the radical and transformative nature of Jesus of Nazareth₂s life and mission. The result is a thought-provoking, elegantly written biography with the pulse of a fast-paced novel: a singularly brilliant portrait of a man, a time, and the birth of a religion"--Publisher.